PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Nurcahyani, Ni Made; Adnyani, I.G.A. Dewi (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
This study aims to determine the effect of compensation, motivation, compensation to employee performance, motivation on employee performance and to determine the effect of job satisfaction on the performance of employees at PT. Sinar Bali Sosro factory. This study used a sample saturated with using all employees at PT. Sinar Bali Sosro factory. The method of analysis of this study using path analysis (Path Analysis). Based on the analysis found that the compensation positive effect on job satisfaction, motivation positive and significant impact on job satisfaction, compensation and significant positive effect on employee performance, motivation positive and significant impact on employee performance, job satisfaction and a significant positive effect on employee performance and satisfaction mediate labor compensation and motivation influence on employee performance. Based on the research results, the company PT. Sinar Bali Sosro factory should provide fair compensation, motivating employees with promotion.
Keywords: Compensation, motivation, job satisfaction and employee performance